Preliminary phytochemical investigation on the steam-distilled oil of Tangelo (Citrus paradisi Macf x Citrus reticulata Blanco - Ramirez, Lina P.
The fresh peel from the matured fruits of tangelo (Citrus paradise Macf. X Citrus reticulata Blanco) was steam-distilled using a cleavenger apparatus for oils lighter than water. The fresh peel was found to contain 2.5% essential oil. The physical and chemical properties of the oil were determined and the sample was subjected to thin layer chromatography and ultraviolet spectrophotometry.